CCAAT/Enhancer-Binding Protein α Is a Crucial Regulator of Human Fat Mass and Obesity Associated Gene Transcription and Expression. (29th April 2014) - Ren, Wei; Guo, Jianjin; Jiang, Feng; Lu, Jun; Ding, Ying; Li, Aimei; Liang, Xiubin; Jia, Weiping
Abstract : Several susceptibility loci have been reported associated with obesity and T2DM in GWAS. Fat mass and obesity associated gene (FTO) is the first gene associated with body mass index (BMI) and risk for diabetes in diverse patient populations. FTO is highly expressed in the brain and pancreas, and is involved in regulating dietary intake and energy expenditure. While much is known about the epigenetic mutations contributing to obesity and T2DM, less is certain with the expression regulation of FTO gene. In this study, a highly conserved canonical C/EBP α binding site was located around position −45~−54 bp relative to the human FTO gene transcriptional start site. Site-directed mutagenesis of the putative C/EBP α binding sites decreased FTO promoter activity. Overexpression and RNAi studies also indicated that C/EBP α was required for the expression of FTO. Chromatin immunoprecipitation (ChIP) experiment was carried out and the result shows direct binding of C/EBP α to the putative binding regions in the FTO promoter. Collectively, our data suggest that C/EBP α may act as a positive regulator binding to FTO promoter and consequently, activates the gene transcription.